Endpoints for extraintestinal manifestations in inflammatory bowel disease trials: the EXTRA consensus from the International Organization for the Study of Inflammatory Bowel Diseases. (March 2022) - Guillo, Lucas; Abreu, Maria; Panaccione, Remo; Sandborn, William J; Azevedo, Valderilio F; Gensler, Lianne; Moghaddam, Bahar; Ahuja, Vineet; Ali, Sabrina A; Allez, Matthieu; Ananthakrishnan, Ashwin N; Bhattacharya, Abhik; et al.
Summary: Extraintestinal manifestations occur frequently in patients with inflammatory bowel disease (IBD) and remain a diagnostic and therapeutic challenge. The aim of the Endpoints for Extraintestinal Manifestations in Inflammatory Bowel Disease Trials (EXTRA) initiative was to achieve international expert consensus on how to assess these manifestations in IBD trials. A systematic literature review was done to identify methods to diagnose extraintestinal manifestations in patients with IBD and measure treatment outcomes. A consensus meeting involving a panel of 41 attendees, including gastroenterologists and referral specialists, was held on March 31, 2021, as part of an International Organization for the Study of Inflammatory Bowel Diseases initiative. The panel agreed that a specialist's expertise is needed to confirm the diagnosis of extraintestinal manifestations before the inclusion of a patient in IBD trials, except for axial spondyloarthritis, for which typical symptoms and MRI can be sufficient. Easy-to-measure endpoints were identified to assess the response of extraintestinal manifestations to treatment without needing specialist involvement. For uveitis, peripheral spondyloarthritis, and arthralgia, endpoint measurements need specialist expertise. The timing of endpoint measurements was discussed for individual extraintestinal manifestations. The EXTRA consensus proposes guidelines on how to thoroughly evaluate extraintestinal manifestations within IBD trials, and recommends that these guidelines are implemented in future trials to enable prospective assessment of these manifestations and comparison between studies.